PS18 Analysis of Emergency 30-Day Readmissions in England Using Routine Hospital Data 2004-2010. Is there Scope for Reduction?. (17th September 2012) - Clarke, A; Blunt, I; Bardsley, M
Abstract : Background: A number of health systems including the NHS have recently introduced arrangements to deny payment if a patient is readmitted to hospital as an emergency soon after a period of care. These approaches assume that emergency admissions are a reflection of poor quality of care and of errors or failure in the original care episode. Our objectives were to assess the extent and types of readmission within 30 days and possible causes and scope for reduction. Methods: Retrospective analysis of 83 million routinely-collected national hospital episode statistics (HES) records covering NHS hospitals in England for a 6 year period (2004–10). Records were linked at the individual level using an annonymised person level identifier. Numbers of 30-day readmissions were calculated. We categorised readmissions using pre-defined discharge-admission diagnostic pairs, overall admission patterns and the "Bridges to Health" patient group categories. Results: There were 7, 166, 304 emergency 30-day readmissions over a six year period equivalent to 8.7% of all hospital discharges. Readmissions were grouped into six categories: Potentially preventable (probable or possible suboptimal care during index admission): 1, 988, 967 (27.8%); Approach to care (anticipated but unpredictable hospital care): 1, 503, 282 (21.0%); Preference of patients or staff in admission or discharge timing: 56, 514 (0.8%); Artefact in data collection: 139, 508(2%); Accident or Coincidence: 1, 473, 583 (20.6%); No obvious cause: 2, 107, 339 (29.4%) Conclusion: Very large numbers of emergency readmissions fell into potentially preventable categories and to categories amenable to immediate reduction by hospitals. Denial of payment for emergency readmission has the potential to improve quality of care by improving data systems and reducing error. Action to address the majority of emergency readmissions requires assessment of care delivery across health and social care providers for those with complex, chronic or terminal conditions. In conclusion, new systems of denial of payment will be dangerous if they invoke perverse incentives which reduce access to necessary hospital care for patients.